Discursos e não-discursos do isso: passarofes de uma escola do campo, inadubações e lesbianidades CIS - Ribeiro, Raoany de Souza (2018)
The research investigates the cisgender lesbians (the it), through the discourses and no-discourses of eight Birdteachers (teachers) of a school of the field of the municipality of Francisco Beltrão / PR. There are six high school birdteachers, one of the fundamental and one birdteachers that works with a project in the school researched more than 20 years. The work is qualitative, through the method: case study, with Foucaultian theoretical contribution. The text has a non-binary writing with words and concepts created or metaphorized. Visits were carried out at the school, questionnaire, open interviews with birdteachers and coexistence with birdemployees (employees), birdstudents (students) and birdprincipal (school principal). The dissertation also had influence of the anthropologist Geertz, then, the culture is emphasized, next to its symbols expressed like means that initiated the research and that helped in the investigations. It was perceived that researching sexuality in the reality of a rural school requires sensitivity and deconstruction of a colonial thought, especially on the parameters of the urban school. We also consider that this is lived as the community manages to negotiate with its neighbors and the school. All of these birdteachers have reported that they might not know and would not be able to deal with lesbian issues in the classroom, we take into account that projections of future possibilities can modify the present and fertilize (give importance, value) a previously unadvised opposite of fertilizing). They also portrayed a scarcity of the subject at undergraduate level, continuing education, as well as knowing only one case of an alleged lesbian kiss among elementary school girls, but that there was no deepening. The discomfort was not clear when being questioned of something that never approached in the formation, nor in the classroom, however, do we perceive interest and curiosity of its parts. Above all, the perceptions were provoked when we talked about the subject and when we discourse about it, which is the speech by the non-speech too. We will hope that the interpretations allow good fertilization to minimize the real difficulties of the birds, as well as to promote resistance against lesbophobia in the rural schools, given their values and specificities on land, means of production, religion, schooling and community.